Efficacy of an air curtain system for local pit environmental control for relic preservation in archaeology museums. Issue 1 (February 2016) - Luo, Xilian; Gu, Zhaolin; Yu, Chuck; Ma, Tao; Kase, Kiwamu
Indoor environmental control has been proven to be a critical consideration for preserving in situ unearthed relics in archaeology museum. An air curtain system has been proposed to separate the local environment of funerary pit from its large-space exhibition hall. The isolation efficiency of the air curtain is formulated by using stream function method in this study. The geometrical dimensions and jet flow parameters were investigated in this study through the theoretical formula, to determine their effects on the isolation efficiency and suitable operation mode, respectively. An experimental setup was constructed to investigate the performance and validate the feasibility of an air curtain system for preservation of historical terracotta figurines in their semi-exposed pits in the exhibition hall. The experimental results showed that the air curtain system could be orientated to isolate the relics or buried treasures unearthed in pits from the large open space of the exhibition hall. These results have significant implications for protecting the relics from deterioration in a control environment of a national museum and will contribute towards sustainable protocol for long-term preservation of unearthed relics in archaeology museums.